Hepatic hyperplasia and damages induces by zearalenone Fusarium mycotoxins in BALB/c mice - Chatopadhyay,Pronobesh (2012)
CONTEXT: Zearalenone is a mycoestrogen and considered a mycotoxin. OBJECTIVE: To establish whether zearalenone produced hepatotoxicity via oral administration. METHODS: Zearalenone was orally administered at a dose of 50 mg, 100 mg and 200 mg ZEN/body weight/daily, respectively, for 14 days to three groups of BALB/c mice. Diagnostic modalities used to evaluate hepatic damage and impaired hepatic function pre- and post zearalenone administration included hepatic marker enzyme activity, pentobarbital sleeping time, cytochrome P-450 activities and histopathologic evaluation of liver. RESULTS: Significant histopathologic changes viz. sinusoidal congestion, cytoplasmic vacuolization, hepatocellular necrosis and neutrophil infiltration were observed after evaluating of liver section from each group after accumulated zearalenone exposure. Further, zearalenone exposure increased activities of alanine transaminase, aspartate transaminase and lipid peroxides whereas activities of tissue glutathione and cytochrome P450 were decreased as compared to control mice. Zearalenone also increased the sleeping time and decreased sleeping latency after pentobarbital through intraperitoneal route as compared to control mice which indicates that the impairment of hepatic metabolizing enzymes by zearalenone. CONCLUSION: Zearalenone is a potential hepatotoxin by oral route.